Bookish. [Season 1] [videorecording (DVD)] - Gatiss, Mark (PBS Distribution, 2026)
"London 1946. The appropriately named Gabriel Book owns a bookshop in Archangel Lane. His wartime was packed with espionage and secrets and he finds that his peace time is just as full of adventure. Now, he helps the police solve the strangest of crimes and the knottiest of murders, but the time he spends with the force is not without its dangers. For although he is very happily married to his childhood best friend, the captivating Trottie, Book is a gay man living at a time when homosexuality was illegal. When Book and Trottie take in Jack, it seems like an act of altruism: a second chance for a young jailbird. Jack proves a worthy assistant both in the shop and in Book's murder investigations, but it soon becomes clear that Jack's appointment wasn't quite as random as it first seemed." --